SOIL MOVEMENT ANALYSIS BASED ON MAXIMUM SOIL SPEED PATTERNS DUE TO THE LOMBOK EARTHQUAKE - Maulidsandy, Penta Adenata; Lepong, Piter; Mislan, Mislan (GEOSAINS KUTAI BASIN, 2022)
ABSTRACT Earthquake activity in Lombok, West Nusa Tenggara (NTB) gives rise to ground movement, this ground movement can be used to predict the intensity of the next earthquake. The purpose of this study is to determine the movement of land based on the pattern of maximum soil velocity that occurred due to the Lombok Earthquake July 29, 2018, which can be used to predict the intensity of the next earthquake. This study uses secondary earthquake data (magnitude) obtained from the USGS (United States Geological Survey). Magnitude data were analyzed using empirical formulas so that the values ​​of intensity, maximum ground velocity and contour maps were obtained. The results show that the movement of the land due to the earthquake moved very quickly towards the north, quickly towards the east, quickly towards the south and finally to the south slowly. The highest maximum ground velocity located in Obel-Obel Village with the value of 23,2 cm / s. The calculation result in the form of this maximum ground velocity can be used as a parameter to predict the upcoming earthquakes that will occur at Lombok or the other side of world.